Comparative Analysis of Zoomlion and YTO Chinese Tractors’ Operational Properties - G. A. Iovlev; V. V. Pobedinskiy; I. I. Goldina (Сельскохозяйственные машины и технологии)
The relevance of the information on the technical capabilities of new tractors being launched into the Russian market is confirmed. (Research purpose) To compare the operational properties of China's Zoomlion and YTO agricultural tractors, and prepare recommendations for domestic agricultural producers. (Materials and methods) The previous research was summarized and analysed, with a special attention on the definition and comparative analysis of the operational properties of Belarus family tractors and foreign tractors, including those made in China. The following methods were used: calculation, comparison, forecasting, economic and mathematical modeling, expert assessments and others. Mathematical dependencies were used to determine the tractor pulling and traction properties, the productivity of machine-tractor units, and specific fuel consumption. (Results and discussion) The operational properties of Zoomlion and YTO tractors were grouped into the categories of approximately equal power, and studied. The performance indicators of the machine-tractor unit were compared during the technological operation "cultivation", as well as its specific fuel consumption. The effect of ballast weights was determined. It was found that in the Zoomlion RN904 and YTO-X904 group, the productivity of the former is 2.4 percent higher, and the specific fuel consumption is 5.1 percent lower; in the Zoomlion RN1104 and YTO-X1104 group, the productivity is 4.9 percent higher, and the specific fuel consumption is 3.9 percent higher; in the Zoomlion RS1304 and YTO-X1304 group, the former outperforms by both indicators - by 8.4 and 10.4 percent, respectively; in the Zoomlion RS1604 and YTO-ELG1604 group, this difference is even more pronounced - 21.3 and 15.4 percent, respectively. (Conclusions). It has been proved that in the group of tractors with the engine power of 66.2-95.6 kilowatts, Zoomlion tractor’s productivity is 5.6 percent higher than that of YTO, and the specific fuel consumption is 4.2 percent lower. It was determined that in the group with the engine power of 117.7 kilowatts, the operational properties are better for YTO.